Pelatihan Pembuatan Produk Olahan Sampah Organik Kepada Ibu-Ibu PKK Dliko Indah, Blotongan, Salatiga - Susanti P. Hastuti; Sucahyo Sucahyo; Rully A. Nugroho; Agna S. Krave; Andreas B.A. Sukmana; V. I. Meitiniarti; Sri Kasmiyati; Elizabeth B.E. Kristiani; Natalia R. Keliat; Desti C. Cahyaningrum; Risya P. Situmorang; Marisa C. Tapilouw; Djohan Djohan; Risky H. Poluan; Cocok A.M. Berutu; Marchella G. Putricia; Easter G. Tuandali; Ciputra S. Mangesa; Shabrina R.A. Fernanda; Imel T.Y. Zebua (LPPM Uncen, 2026)
Knowledge regarding the handling of waste generated by human activities—and familiarity with the associated technologies—has not yet widely reached housewives. This is due to constraints on their time and energy, as well as a lack of hands-on exposure to these technologies within the household setting. Public understanding regarding the composition of waste (both dry and wet) remains limited, and there is a prevailing tendency—particularly in terms of attitudes and behavior—to rely on the government for waste management. Although the potential for utilizing organic waste is immense, implementation at the community level faces obstacles such as regulatory issues, technological limitations, and low collective awareness. Therefore, it is urgent to enhance knowledge and develop technologies for converting organic waste into value-added products, especially for housewives who deal with organic waste generation on a daily basis. The partners for this activity are 65 housewives who are members of the PKK (Family Welfare Empowerment) group in RT01/RWXI Dliko Indah, Blotongan, Salatiga. The implementation team comprises fifteen lecturers and five students from the Biology study program. The program is executed in two stages: a preparation phase and a product production phase. The preparation phase involves initial planning by the community service team in coordination with the partners. The product production phase entails material preparation and the creation of products such as compost, liquid organic fertilizer (POC), and eco-enzymes. These activities include hands-on practice, followed by continuous monitoring to evaluate the program's success.